Wound Healing Potential of Apium graveolens L. Extract through IL-1 Suppression and PDGF Upregulation - Apriliana, Harvina Dwi; Setiawan, Eko; Chodidjah, Chodidjah (Faculty of Medicine, Universitas Diponegoro, 2026)
ABSTRACTBackground: Incised wounds from sharp objects disrupt skin function and risk infection. Healing involves cytokines like IL-1 and growth factors like PDGF. Celery leaf extract (Apium graveolens L.), rich in flavonoids, saponins, and tannins, shows anti-inflammatory and pro-angiogenic effects that may lower IL-1 and boost PDGF.Objective: To evaluate the effect of celery leaf extract cream on IL-1 levels and PDGF expression in male Wistar rats with incised wounds.Methods: This in vivo experimental study employed a post-test only control group design. Thirty male Wistar rats were divided into five groups: healthy control, negative control (cream base), positive control (10% povidone iodine), 2% celery extract cream, and 4% celery extract cream. Incised wounds were made on the rats’ backs, and the cream was applied once daily for 7 days. IL-1 levels were analyzed using ELISA, while PDGF expression was measured using qRT-PCR. Data were analyzed with the Kruskal-Wallis and Mann-Whitney tests (p<0.05).Results: The lowest mean IL-1 level in the treatment groups was found in the 4% celery extract cream group (5.80 ± 1.19 ng/mL), while the highest was in the povidone iodine group (6.77 ± 0.51 ng/mL). The Kruskal-Wallis test showed a significant difference among all groups (p=0.009). The highest mean PDGF expression was observed in the 2% celery extract cream group (3.10 ± 3.18), followed by povidone iodine (2.53 ± 4.37), whereas the 4% celery extract cream group had a value of 0.57 ± 0.66. However, the differences among groups were not statistically significant (p=0.279).Conclusion: Administration of celery leaf extract cream reduced IL-1 levels in the treatment groups; however, the increase in PDGF expression did not show significant differences among the Wistar rat incisional wound model groups.